The historical collection, King George VI Art Gallery, Port Elizabeth - Forster-Towne, Rosemary (Rhodes University, Faculty of Humanities, Department of Fine Art, 1984)
From Conclusion: For the sake of posterity and historical research, our need for secure origins and our appreciation of and pleasure in fine craftsmanship and art, it is important that any Art Collection, particularly an Historical one, be fully documented. All data pertaining to the pictures should be recorded from an artistic, historical and even scientific point of view and photographs should be taken of the pictures. An organized classification system, the correct registering and labeling of each picture and its accessioning and cataloguing as part of the contents of the Gallery and for visitors information, should be constantly 53 maintained and where necessary and in as many ways as possible, cross-references made so that the stored information be usable. To this end and with the growth and increasing importance being placed on Art Museums and Galleries in the community it would probably be of value to cross-reference with other similar institutions and in the respect and day and age, it is not unrealistic to propose that the King George VI Art Gallery consider a computer cataloguing system to facilitate research and complement a more simplified version for the use and guide of the general viewing public . The significance of a picture is not only its value as such, but also the information relating to it. The importance of the Historical Collection as Africana and works of art, expressive of the places, events, people and even attitudes, and as cultural and historic items, goes without saying. Without the Historical Collection of the King George VI Art Gallery, Port Elizabeth, the Eastern Cape community and South Africa too, would be the poorer. The pictures have their role to play .
Keywords: Art museums -- South Africa Port Elizabeth; Art, Modern 20th century History; King George VI Art Gallery; Art, -- South African 20th century Exhibitions